Non-reductive modulation of chloroplast fructose-1,6-bisphosphatase by 2-Cys peroxiredoxin - Caporaletti, Daniel Ernesto (2007)
2-Cys peroxiredoxin (2-Cys Prx) is a large group of proteins that participate in cell proliferation, differentiation, apoptosis, and photosynthesis. In the prevailing view, this ubiquitous peroxidase poises the concentration of H2O2 and, in so doing, regulates signal transduction pathways or protects macromolecules against oxidative damage. Here, we describe the first purification of 2-Cys Prx from higher plants and subsequently we show that the native and the recombinant forms of rapeseed leaves stimulate the activity of chloroplast fructose-1,6-bisphosphatase (CFBPase), a key enzyme of the photosynthetic CO2 assimilation. The absence of reductants, the strict requirement of both fructose 1,6-bisphosphate and Ca2+, and the response of single mutants C174S and C179S CFBPase bring forward clear differences with the well-known stimulation mediated by reduced thioredoxin via the regulatory 170's loop of CFBPase. Taken together, these findings provide an unprecedented insight into chloroplast enzyme regulation wherein both 2-Cys Prx and the 170's loop of CFBPase exhibit novel functions